2016
DOI: 10.1063/1.4961558
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the new multichannel X-mode edge density profile reflectometer for the ICRF antenna on ASDEX Upgrade

Abstract: A new multichannel frequency modulated continuous-wave reflectometry diagnostic has been successfully installed and commissioned on ASDEX Upgrade to measure the plasma edge electron density profile evolution in front of the Ion Cyclotron Range of Frequencies (ICRF) antenna. The design of the new three-strap ICRF antenna integrates ten pairs (sending and receiving) of microwave reflectometry antennas. The multichannel reflectometer can use three of these to measure the edge electron density profiles up to 2 x 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 6 publications
0
27
0
Order By: Relevance
“…Theoretical approaches [24][25][26] to model sheaths are being developed and will be validated against measurements on ASDEX Upgrade [11,27] and on IShTAR [28,29]. Theoretical insight of experimental results will provide key guidelines to design antennas with reduced sheaths and RF-induced impurities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical approaches [24][25][26] to model sheaths are being developed and will be validated against measurements on ASDEX Upgrade [11,27] and on IShTAR [28,29]. Theoretical insight of experimental results will provide key guidelines to design antennas with reduced sheaths and RF-induced impurities.…”
Section: Discussionmentioning
confidence: 99%
“…The recent results have shown that compared to 2-strap antennas, the use of 3-strap antennas reduces the RF-specific tungsten release significantly [10]. The SOL density convection due to the inhomogeneous RF-sheath potential was measured with poloidally distributed reflectometers embedded in one 3-strap antenna [11]. The measured density convection can clearly be reproduced in the self-consistent simulations by running the EMC3-EIRENE, RAPLICASOL and SSWICH [12] codes in an iterative way [13].…”
Section: Introductionmentioning
confidence: 93%
“…The probing frequency at which the first reflection occurs is called the First Fringe (FF) frequency and indicates the start of the group delay measurement of the X-mode upper cut off reflection. This first reflection occurs when the plasma electron density is n e ≈ 0, and when the propagating wave's frequency matches the local electron cyclotron frequency limit f = f + ce , as determined from (1). The group delay measurement starts at this FF frequency and is proportional to the beat frequency of the acquired signal divided by the probing frequency variation rate τ g = f b (dt/df ).…”
Section: Introductionmentioning
confidence: 91%
“…The data outside the ROI is zeroed out, resulting in the preprocessed input spectrogram image shown in Figure 7. The true FF frequency value is discretized into a one-hot vector 1 with 1120 possible discrete values between 40 GHz and 64 GHz (signal quality decreases above 64 GHz), resulting in 21 MHz FF frequency resolution versus the original 93.5 MHz probing frequency resolution of the spectrogram. There is a trade off between acceptable discretization resolution and FF coverage of the training dataset.…”
Section: B Preprocessing and Extending The Datasetmentioning
confidence: 99%
See 1 more Smart Citation